Involvement of kallikrein‐PAR2‐proinflammatory pathway in severe trastuzumab‐induced cardiotoxicity. Issue 10 (19th August 2022) - Sasaki, Ritsuko; Kurebayashi, Nagomi; Eguchi, Hidetaka; Horimoto, Yoshiya; Shiga, Takahiro; Miyazaki, Sakiko; Kashiyama, Taku; Akamatsu, Wado; Saito, Mitsue
Abstract: Trastuzumab‐induced cardiotoxicity interferes with continued treatment in approximately 10% of patients with ErbB2‐positive breast cancer, but its mechanism has not been fully elucidated. In this study, we recruited trastuzumab‐treated patients with ≥30% reduction in left ventricular ejection fraction (SP) and noncardiotoxic patients (NP). From each of these patients, we established three cases of induced pluripotent stem cell‐derived cardiomyocytes (pt‐iPSC‐CMs). Reduced contraction and relaxation velocities following trastuzumab treatment were more evident in SP pt‐iPSC‐CMs than NP pt‐iPSC‐CMs, indicating the cardiotoxicity phenotype could be replicated. Differences in ATP production, reactive oxygen species, and autophagy activity were observed between the two groups. Analysis of transcripts revealed enhanced kallikrein5 expression and pro‐inflammatory signaling pathways, such as interleukin‐1β, in SP pt‐iPSC‐CMs after trastuzumab treatment. The kallilkrein5‐protease‐activated receptor 2 (PAR2)‐MAPK signaling pathway was more activated in SP pt‐iPSC‐CMs, and treatment with a PAR2‐antagonist suppressed interleukin‐1β expression. Our data indicate enhanced pro‐inflammatory responses through kallikrein5‐PAR2 signaling and vulnerability to external stresses appear to be the cause of trastuzumab‐induced cardiotoxicity in SP. Abstract : Using the induced pluripotent stem cell‐derived cardiomyocytes model generated from patients with severe trastuzumab‐induced cardiotoxicity, we newly found that the toxicity may be attributed to increased pro‐inflammatory responses mediated through an enhanced kallikrein5‐PAR2 signaling pathway.